Meningkatkan Motivasi Belajar Matematika Menggunakan Penerapan Pendekatan Culturally Responsive Teaching (CRT) Berbantuan Quizizz Paper Mode pada Materi Eksponen Kelas X di SMAN 21 Surabaya - Asrita Fahruni Misbakh; Suhartono Suhartono; Isnaini Abdullah (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study aims to increase motivation to learn mathematics by using the Culturally Responsive Teaching (CRT) approach assisted by Quizizz Paper Mode on class X exponential material at SMAN 21 Surabaya. Learning motivation is one of the important factors in achieving students' academic success. The low motivation of students to learn in mathematics subjects is the background of this research. This type of research is Classroom Action Research (PTK) which is carried out during 2 learning cycles. The data collection techniques used are observation and questionnaires. The results of the study show that the application of the Culturally Responsive Teaching (CRT) approach assisted by Quizizz Paper Mode can increase students' motivation to learn mathematics. The increase can be seen from the increase in the percentage of students' learning motivation in the first cycle of 80.9% with a high category and the percentage of students' learning motivation in the second cycle of 90.93% with a very high category. The result of the increase in learning motivation from cycle I to cycle II was 10.03%.